2020
DOI: 10.1071/ch19557
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Classification of Three-Centre Two-Electron Bonds

Abstract: We evaluate the three-centre two-electron (3c-2e) bonds using atoms in molecules (AIM) and natural bond orbital (NBO) theoretical analyses. They have been classified as ‘open (V)’ or ‘closed (Δ)’, depending on how the three centres were bonded. Herein, we show that they could be classified as V, L, Δ, Y, T and I (linear) arrangements depending on the way the three centres are bonded. These different structures are found in B2H6 (V), CH5+ (V), Me-C2H2+ (L), B3+ (Δ), C3H3+ (Δ), H3+ (Y), 2-norbornyl+ (T), SiH5+ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…structure 7 C ). 26 Simultaneously, the former π contributions of the C 2 fragment gradually merge into a newly formed B(sp 2 )–C σ orbital at the distal olefinic C atom. Finally, the 2e3c-bond orbital transforms to a pure E(sp 3 )–C σ-bond orbital.…”
Section: Resultsmentioning
confidence: 99%
“…structure 7 C ). 26 Simultaneously, the former π contributions of the C 2 fragment gradually merge into a newly formed B(sp 2 )–C σ orbital at the distal olefinic C atom. Finally, the 2e3c-bond orbital transforms to a pure E(sp 3 )–C σ-bond orbital.…”
Section: Resultsmentioning
confidence: 99%
“…66,67 The trihydrogen cation (the simplest triatomic ion, detected more than a hundred years ago 68 ) is a symmetric triangular cation with a non-nuclear attractor in its center. 69–71 The ethenium cation, represents an example of a conflict structure as a bond critical point (BCP) connects H + with a BCP between two carbon atoms. Similar situation was recently observed by Gnanasekar and Arunan in SiH 5 + .…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to stress that our results, which consider that MMBs in PCMs and in the Ah and Ai phases of group-15 and -16 elements are equivalent to EDMBs in boranes and also in the polymeric HP phases of nitrogen and hydrogen, are in contradiction with previous assumptions [88] that suggested that ERMBs should occur at HP for elements of groups 14-18 of the periodic table since typical hypervalent molecules with this kind of bond, such as I3 ꟷ , XeF2, XeF4, and XeF6 [81,82], correspond to elements of these groups. Note that the EDMB formation was previously assumed [88] to occur for elements of groups 1, 2, and 13 since they are present in typical molecules with this kind of bond, such as H3 ꟷ , B2H6, and Al2H7 ꟷ [54,61].…”
Section: Nature Of Metavalent Multicenter Bondingmentioning
confidence: 99%
“…In this respect, Wuttig and coworkers left open the door for metavalent bonds to be equivalent to charge-shift bonds [60], or even to electron-deficient multicenter bonds (EDMBs). In particular, EDMBs are akin to three-center-two-electron (3c-2e) bonds present in boranes [54,61] and in solids, such as boron [27], boron-based compounds [62], intermetallics [63], and some aluminosilicates [64]. Contrarily, Jones et al [59] insisted that metavalent bonds are indeed ERMBs and that the ES value is not a good parameter to describe the unconventional bonding in PCMs.…”
Section: Introductionmentioning
confidence: 99%